High-performance stacked in-plane supercapacitors and supercapacitor array fabricated by femtosecond laser 3D direct writing on polyimide sheets. (1st July 2017) - Wang, Shutong; Yu, Yongchao; Li, Ruozhou; Feng, Guoying; Wu, Zili; Compagnini, Giuseppe; Gulino, Antonino; Feng, Zhili; Hu, Anming
Abstract: We demonstrate the fabrication of in-plane and multi-layer 3D micro-supercapacitors (MSCs) based on laser carbonization of polyimide (PI) sheets. Focused femtosecond (fs) laser pulses rapidly convert the insulating PI into an electrically conductive porous carbon structure. The specific capacitance of the single-layer supercapacitor with a thickness of 80 μm reaches 22.40 mF/cm 2 (2.8 F/cm 3 ) at 0.1 mA/cm 2 charge-discharge current density. The high performance is attributed to hierarchical porous structures and the appropriate heteroatom nitrogen/oxygen doping. The 2-layer and 3-layer stacked MSCs show an improved specific capacitance as high as 37.2 mF/cm 2 and 42.6 mF/cm 2 at a current density of 0.1 mA/cm 2, respectively, which are attractive values among the carbon material-based MSCs reported till now. The voltage and capacitance can be scaled up by simply writing MSC arrays in serial and parallel connections. The facile fabrication and superior performance of carbon-based MSCs fabricated by laser direct writing may pave the way for promising applications of flexible, portable, and wearable electronic devices.